Exploring English Teachers’ Views on the Compulsory English Subject for Non-English Major Students: A Case Study at an Indonesian University - Saifullah, Saifullah; Yawan, Hendri (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
This research investigates the perspectives of English teachers regarding the factors influencing the teaching and learning of English as a compulsory subject, specifically the English conversation course (Matakuliah Institusi), for non-English major students at Dayanu Ikhsanuddin University in Baubau. The study employed semi-structured interviews with six English teachers affiliated with the English study program at the university. By examining both positive and negative aspects, the research aimed to identify the factors that impact the quality of instruction and learning in the English conversation course. The findings highlight several factors, including the syllabus, availability of resources and equipment, students' attitudes and motivation towards learning English, participation in extracurricular activities, class size, institutional support, and teachers' enthusiasm. These factors were identified by the teachers as having both positive and negative influences on the course. Furthermore, the English teachers were given the opportunity to provide suggestions for program improvement, such as emphasizing the importance of support and commitment from the heads of each study program.